A New Look at b → s Observables in 331 Models - Francesco Loparco (Particles, 2024)
Flavour changing neutral current (FCNC) processes are described by loop diagrams in the Standard Model (SM), while in 331 models, based on the gauge group <semantics>SU(3)C×SU(3)L×U(1)X</semantics>, they are dominated by tree-level exchanges of a new heavy neutral gauge boson <semantics>Z′</semantics>. By exploiting this feature, observables related to FCNC decays of K, <semantics>Bd</semantics> and <semantics>Bs</semantics> mesons can be considered in several variants of 331 models. The variants are distinguished by the value of a parameter <semantics>β</semantics> that plays a key role in this framework. Imposing constraints on the <semantics>ΔF=2</semantics> observables, we select possible ranges for the mass of the <semantics>Z′</semantics> boson in correspondence to the values <semantics>β=±k/<msqrt>3</msqrt></semantics>, with <semantics>k=1,2</semantics>. The results are used to determine the impact of 331 models on <semantics>b→s</semantics> processes and on the correlations among them, in the light of new experimental data recently released.